2003
DOI: 10.1301/nr.2003.aug.272-279
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Action of Dietary Fatty Acids in Regulating the Activation of Vascular Endothelial Cells during Atherogenesis

Abstract: Dietary long chain omega-3 polyunsaturated fatty acids from fish oil appear to be clearly efficient in regulating endothelial dysfunction (or activation), which is the first stage of atherogenesis. Studies on endothelial cells in vitro have shown that the main dietary PUFA and oleic acid may prevent endothelium activation either by inhibiting the expression of adhesion molecules or by improving the nitric oxide production. Saturated fatty acids and also linoleic acid do not inhibit endothelium activation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 71 publications
0
29
0
4
Order By: Relevance
“…In contrast to other long-chain fatty acids, oleic acid is rather ineffective at inducing cellular oxidative stress (64). However, oleic acid has been reported to increase the production of NO in endothelial cells (65). Because both superoxides and NO are needed for peroxynitrite formation, it seems reasonable that the level of nitrotyrosine is unaltered upon treatment with oleic acid in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other long-chain fatty acids, oleic acid is rather ineffective at inducing cellular oxidative stress (64). However, oleic acid has been reported to increase the production of NO in endothelial cells (65). Because both superoxides and NO are needed for peroxynitrite formation, it seems reasonable that the level of nitrotyrosine is unaltered upon treatment with oleic acid in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Oleic acid may prevent endothelium activation either by inhibiting the expression of adhesion molecules or by affecting nitric oxide production (Christon, 2003). The presence of carotenoids in PSO (Younis et al, 2000) may share in the cardio-protective effect as reported previously (Melendez-Martinez et al, 2004).…”
Section: Discussionmentioning
confidence: 55%
“…Tsimikas et al (1999) explained the mechanism by which oleic acidenriched diets decreased lipoprotein susceptibility to oxidation, presumably, as a result of the decreased linoleic acid content within lipoproteins. Studies on endothelial cells in vitro have shown that dietary oleic acid may prevent endothelium activation either by inhibiting the expression of adhesion molecules or by affecting nitric oxide production (Christon, 2003). Supplementation of endothelial cells with oleic acid in vitro reduces endothelial cell sensitivity to oxidants, creating a reduced prooxidant environment as a consequence of reduced intracellular RoS (Spolarics, 1996).…”
Section: Resultsmentioning
confidence: 99%